Tuberculous Meningitis in an Immunocompetent Host: A Diagnostic Challenge - Hussein Algahtani; Bader Shirah; Nawal Abdelghaffar; Abdulrahman J. Alqahtani; Mohammad Alshehri (Dr. Sulaiman Al Habib Medical Journal)
Tuberculosis is a major global public health problem, which poses significant diagnostic and treatment challenges. Tuberculous meningitis is the most severe form of extrapulmonary tuberculosis, which approximately affects 1% of all patients with active tuberculosis. It is considered a medical emergency as it causes neurological deficits in more than half of those affected and may lead to death despite advancement in antituberculous medications. In this article, we are reporting a challenging case of tuberculous meningitis with a delay in diagnosis and initiation of treatment. In addition, we summarize the challenges regarding the diagnosis and management of this disease. Although central nervous system tuberculosis is rare in immunocompetent hosts, such cases can be seen in neurology practice and represent a major clinical and diagnostic challenge. Although this case is not an uncommon scenario and no alternative diagnosis is suspected, the patient was not started on antituberculous medications because of an unjustified request for pathological diagnosis by the admitting team. Although Saudi Arabia is not one of the 22 countries with the highest number of tuberculosis cases worldwide, tuberculosis continues to represent a major health problem. Treating clinicians should try to use methods to increase the mycobacterial yield of cerebrospinal fluid smear examination. Multidisciplinary care, not a one-man show, should be practiced with cooperation and exchange of opinions between neurologists, infectious diseases specialists, neurosurgeons, and intensivists. Brain or meningeal biopsy is not a routine investigation tool and should never delay the initiation of antituberculous medications. Despite advancements in the field of tuberculosis science, it continues to represent a clinical and diagnostic challenge with a substantial percentage of morbidity and mortality.